Mindfulness-based stress reduction is linked with an improved Cognitive Reflection Test score - Lachaud, Léa; Jacquet, Baptiste; Bourlier, Maxime; Baratgin, Jean (Frontiers in Psychology, 2023)
Initially, dual-process theories suggested that the existence of two different cognitive systems explained why many participants do not find the correct answer in many reasoning tasks. The Cognitive Reflection Test (CRT) is one such task. It contains three questions with incorrect answers (typically associated with intuition and thus system 1 which processes information automatically) and correct answers (typically associated with deliberate thinking and thus system 2 which involves the conscious processing of information). More recent theories suggest system 1 is responsible for both incorrect and correct responses, with system 2 being used to resolve the conflict between these different intuitions. Since mindfulness training improves self-regulation and cognitive flexibility, we believe it could improve CRT scores by reducing the relative weight of initial intuitions by strengthening alternative intuitions, thus increasing the probability of triggering deliberate reasoning. To test this hypothesis, we recruited 36 participants, all registered in the same Mindfulness-Based Stress Reduction (MBSR) training. Of those 36 participants, 18 answered the CRT before the training and 18 answered it after 8 weeks of training. Results show that participants who followed MBSR training had better CRT scores than those without training. This is coherent with our hypothesis that mindfulness training could reduce the relative weight of initial intuitions and facilitates deliberate thinking.